Modeling the structure-reactivity relationship of acrylates - Değirmenci, İsa. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
Photoinitiated polymerization of acrylates is one of the most common processes for therapid production of polymeric cross-linked materials with defined properties. Acrylicmonomers have different reactivity behavior during the free radical polymerization depending on the position of substituents on the monomer. In this study, the free radical polymerizationof alkyl ??-hydroxymethyl acrylates, itoconic acid derivatives and substituted methyl acrylatesare modeled by using the ab initio (B3LYP/6-31G*) quantum mechanical calculations.Transition states for the radical addition, the chain transfer and the disproportionation reactions are located. The reaction rates are calculated by using the classical Transition StateTheory in order to understand the structure-reactivity relationship of acrylates. The variablessuch as the activation energies, the entropy of transition states and the Boltzmann averageddipole moments of the monomers are discussed. The lability of the hydrogen atoms in the monomers and radicals has been determined. The disproportionation rate constant, kd, is usedin the kp/kt1/2 ratio to evaluate the rate of polymerization. It has been found that in generalbulky groups decrease the rate of polymerization while electron withdrawing substituents and polar molecules enhance the polymerizability of the monomers.
Keywords: Acrylates.; Polymerization.